The development of a multidimensional scale to evaluate motor vehicle dynamic qualities. - Harris, Don; Chan-Pensley, J; McGarry, S (Taylor & Francis, 2005)
Advances in motor vehicle engineering will allow greater refinement of the dynamic qualities of passenger cars in the near future. This paper describes the development and initial validation of a reliable and valid multidimensional scale to assess these parameters based upon a technique previously developed to evaluate aircraft handling qualities. The scaling methodology developed emphasizes the interaction between the vehicle's dynamic behaviour and the category of vehicle (e.g. sports car, executive saloon). This three-part study describes the initial extraction and the subsequent verification of the scale dimensions from an analysis of the opinions of circa 500 drivers, followed by an evaluation of the sensitivity and diagnosticity of the scale to distinguish between the road behaviour exhibited by vehicle types. The results suggest that the scale shows both content and construct validity, being able to distinguish both between broad categories of vehicle and different models of vehicle within a particular category in a consistent and meaningful manner.